Uji Konsentrasi Nematoda Entomopatogen Steinernema carpocapsae Weiser Lokal terhadap Hama Penggerek Tongkol Jagung Helicoverpa armigera Hubner di Laboratorium - Desita Salbiah; Mutiara Kusuma Wardani (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2026)
[CONCENTRATION OF LOCAL ENTOMOPATHOGENIC NEMATODE Steinernema carpocapsae Weiser AGAINST CORN COB BORER Helicoverpa armigera Hübner IN LABORATORY BIOASSAYS]. Corn (Zea mays L.) ranks among Indonesia's most vital food crops. However, production in Riau Province has declined due to infestations by the corn cob borer (Helicoverpa armigera Hübner), which can damage up to 39.7% of crops. Conventional control relies on synthetic chemical insecticides, which pose persistent risks including mortality of natural enemies, pest resistance, and population resurgence. An eco-friendly alternative involves local entomopathogenic nematodes (EPN), Steinernema carpocapsae Weiser, which induce rapid host mortality (within 24–48 hours) via symbiotic bacteria producing lethal toxins. This study determined the best concentration of S.carpocapsae infectious juveniles (IJ) for H. armigera mortality under laboratory conditions. An experimental approach employed a completely randomized design (CRD) with five concentrations (0, 250, 500, 750, and 1000 IJ/mL distilled water) and four replicates per treatment. Parameters assessed included EPN identification, time to initial mortality, and total mortality. Data were subjected to analysis of variance (ANOVA) followed by DNMRT test at 5% significance. Results revealed that 750 IJ/mL was the most effective concentration, achieving 80% total mortality within 72 hours post-application. These findings support S. carpocapsae at 750 IJ/mL as a viable biocontrol agent for H. armigera in integrated pest management (IPM) programs, warranting field trials to validate efficacy under Riau's agroecological conditions.